Pedagogical university students’ ethical attitudes and competences regarding artificial intelligence: An empirical study - Alicja Baum; Maria Trzcińska-Król (Multidisciplinary Journal of School Education, 2025)
Research objectives and problems: The aim of the research was to examine the self-assessment and views of students from a pedagogical university on the ethical and moral aspects of using AI and their relationship with general attitudes toward AI, as well as competences and knowledge in this area.